Anatomical Variations in Relation to Anterior Group of Forearm Muscles - Sharma, M.; Prashar, R. (Recent Developments in Medicine and Medical Research Vol. 14, 2021)
Muscles are notoriously variable, and it is quite common to discover muscular anomalies during routine dissection of the human body. The anterior group of muscles is typically divided into three layers: superficial, intermediate, and deep. The forearm of an 86-year-old embalmed female cadaver was dissected in the department of Anatomy, Punjab Institute of Medical Sciences Jalandhar, during standard upper-limb dissection for medical students. Two variants were noted in this case. Initially, the ulnar nerve in the anterior compartment of the forearm passed through the flexor digitorum profundus muscle before connecting to the flexor carpi ulnaris. Second, there was an accessory muscle with a short belly that was merging with the flexor pollicis longus muscle's tendon. Both variations were found bilaterally. In practise, being aware of man's anatomical variability may prevent surgical errors and inspire new methods of restoration. A thorough knowledge of anatomic variants of nerve will assist the surgeon in avoiding inadvertent placement of retractors that can result in direct injury to the nerve or indirectly through traction.